2006
DOI: 10.1016/j.ijfoodmicro.2006.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Emetic toxin-producing strains of Bacillus cereus show distinct characteristics within the Bacillus cereus group

Abstract: One hundred representative strains of Bacillus cereus were selected from a total collection of 372 B. cereus strains using two typing methods (RAPD and FT-IR) to investigate if emetic toxin-producing hazardous B. cereus strains possess characteristic growth and heat resistance profiles. The strains were classified into three groups: emetic toxin (cereulide)-producing strains (n = 17), strains connected to diarrheal foodborne outbreaks (n = 40) and food-environment strains (n = 43), these latter not producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
76
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(90 citation statements)
references
References 26 publications
13
76
1
Order By: Relevance
“…Endophytic cereulide-producing B. cereus organisms from spruce (Picea abies) were also reported to differ in ribopatterns from the nonproducers (NS61 and NS88 [20]). The potato isolates differed from the spruce tree producers in ribopatterns and modest cereulide production, 1 to 100 ng mg of biomass Ϫ1 compared 900 to 1,700 ng mg of biomass Ϫ1 for the NS strains (Norway spruce [51,52,54]). It might be that each plant species carries its own B. cereus cereulide-producing genotype, possibly adapted to the specific metabolic environment inside the host plant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Endophytic cereulide-producing B. cereus organisms from spruce (Picea abies) were also reported to differ in ribopatterns from the nonproducers (NS61 and NS88 [20]). The potato isolates differed from the spruce tree producers in ribopatterns and modest cereulide production, 1 to 100 ng mg of biomass Ϫ1 compared 900 to 1,700 ng mg of biomass Ϫ1 for the NS strains (Norway spruce [51,52,54]). It might be that each plant species carries its own B. cereus cereulide-producing genotype, possibly adapted to the specific metabolic environment inside the host plant.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, a recent epidemiological survey from Finland indicated that the early introduction of root vegetables in infancy was associated with advanced ␤-cell autoimmunity in young children and increased susceptibility to type 1 diabetes (72). Cereulide-producing B. cereus is known to produce spores that are severalfold more resistant to heating at 90°C compared to B. cereus spores of cereulide-nonproducing B. cereus (52). Such spores are likely to survive and become enriched in foods processed by repeated heating.…”
Section: Discussionmentioning
confidence: 99%
“…It is a common food contaminant and is an etiological agent of two distinct forms of illness, i.e., emetic and diarrheal. Carlin et al (2006) observed different percentages in spore germination at chilled temperatures among B. cereus genetic groups.…”
Section: Introductionmentioning
confidence: 84%
“…Parameter p characterises the shape of the curves: concave curves p < 1, convex curves p > 1 and linear curves p equal 1, in this case  parameter can be assimilated to the traditional D value of thermal resistance curves. This equation was used by different authors (Mafart et al, 2002;Virto et al, 2005;Carlin et al, 2006;Buzrul, 2007) and was implemented in this work as primary model. The shape parameter p variation on the goodness of fit of models was shown by Couvert et al (2005) to have slight influence so that a single pvalue can be used for a given microbial population (same physiological state, same preculture) (Couvert et al, 2005).…”
Section: Campylobacter Infectionsmentioning
confidence: 99%